Productivity and International Firm Activities: What do we know? - Wagner, Joachim (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
This paper summarizes in a non-technical way what we know from empirical studies based on firm-level data about the mutual links between international activities of firms and productivity. It is written with a view to inform policy makers in an evidence-based way. A special focus is on the empirical evidence we have from studies using firm-level data from the Nordic countries. It is argued that this empirical evidence does not provide a sound basis to search for similarities and differences (and their causes) between the Nordic countries, and the empirical results reported cannot qualify as stylized facts that can inform policy makers in an evidence-based way.
Keywords: International Firm Activity; Productivity; Firm Level Data; Nordic Countries; 330 Wirtschaft